Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) Ta có: \(x^3+12x^2+48x+64\)
\(=x^3+3\cdot x^2\cdot4+3\cdot x\cdot4^2+4^3\)
\(=\left(x+4\right)^3\)
b) Ta có: \(x^3-12x^2+48x-64\)
\(=x^3-3\cdot x^2\cdot4+3\cdot x\cdot4^2-4^3\)
\(=\left(x-4\right)^3\)
c) Ta có: \(8x^3+12x^2y+6xy^2+y^3\)
\(=\left(2x\right)^3+3\cdot\left(2x\right)^2\cdot y+3\cdot2x\cdot y^2+y^3\)
\(=\left(2x+y\right)^3\)
d)Sửa đề: \(x^3-3x^2+3x-1\)
Ta có: \(x^3-3x^2+3x-1\)
\(=x^3-3\cdot x^2\cdot1+3\cdot x\cdot1^2-1^3\)
\(=\left(x-1\right)^3\)
e) Ta có: \(8-12x+6x^2-x^3\)
\(=2^3-3\cdot2^2\cdot x+3\cdot2\cdot x^2-x^3\)
\(=\left(2-x\right)^3\)
f) Ta có: \(-27y^3+9y^2-y+\frac{1}{27}\)
\(=\left(\frac{1}{3}\right)^3+3\cdot\left(\frac{1}{3}\right)^2\cdot\left(-3y\right)+3\cdot\frac{1}{3}\cdot\left(-3y\right)^{^2}+\left(-3y\right)^3\)
\(=\left(\frac{1}{3}-3y\right)^3\)
a) \(27x^3+8^3\)
\(=\left(3x\right)^3+2^3\)
\(=\left(3x+2\right)\left[\left(3x\right)^2+6x+2^2\right]\)
\(=\left(3x+2\right)\left(9x^2-6x+4\right)\)
b) \(8x^3-y^3\)
\(=\left(2x-y\right)\left(4x^2+2xy+y^2\right)\)
c) \(x^2+4xy+4y^2\)
\(=\left(x+2y\right)^2\)
\(27x^3+8\)
\(=\left(3x\right)^3+2^3\)
\(=\left(3x+2\right)\left(9x^2-6x+4\right)\)
\(8x^3-y^3\)
\(=\left(2x\right)^3-y^3\)
\(=\left(2x-y\right)\left(4x^2+2xy+y^2\right)\)
\(x^2+4xy+4y^2\)
\(=x^2+2.x.2y+\left(2y\right)^2\)
\(=\left(x+2y\right)^2\)
_Minh ngụy_
a)(x+3y)(x2-3xy+9y2)=x3+27y3
b)(2x-3y)(4x2+6xy+9y2)=8x3-27y3
a)\(2a^3+16=2\left(a^3+8\right)=2\left(a+2\right)\left(a^2-2a+4\right)\)
b)\(8x^3+27y^3+36x^2y+54xy^2=\left(2x\right)^3+\left(3y\right)^3+3.\left(2x\right)^2.3y+3.2x.\left(3y\right)^2\)
\(=\left(2x+3y\right)^2\)
c)\(x^4-2x^3-x^2+2x+1=\left(x^4-x^3-x^2\right)-\left(x^3-x^2-x\right)-\left(x^2-x-1\right)\)
\(=x^2\left(x^2-x-1\right)-x\left(x^2-x-1\right)-\left(x^2-x-1\right)\)
\(=\left(x^2-x-1\right)\left(x^2-x-1\right)=\left(x^2-x-1\right)^2\)
Bài 1 : hđt bạn tự làm nhé
Bài 2 :
\(\left(x-1\right)\left(x^2+x+1\right)-\left(x-4\right)^2x\)
\(=x^3-1-x\left(x^2-8x+16\right)=x^3-1-x^3+8x^2-16x\)
\(=8x^2-16x-1\)
\(\left(x+7\right)\left(x^2-7x+49\right)-\left(5-x\right)\left(5+x\right)\left(x-1\right)\)
\(=x^3+343-\left(25-x^2\right)\left(x-1\right)=x^3+343-\left(25x-25-x^3+x^2\right)\)
\(=x^3+343+x^3-x^2-25x+25=2x^3-x^2-25x+368\)
=23.X3 + 33.Y3
= [2x]3 + [3y]3
= [2x + 3y][4x2 + 6xy + 9y2] = [2x + 3y]3 - 18x2y - 18xy2 = [2x + 3y]3 + 18xy[x + y]
\(8x^3-27y^3=\left(2x\right)^3-\left(3y\right)^3\)
\(=\left(2x-3y\right)\left(4x^2+6xy+9y^2\right)\)